Level of penetration of two medicated pastes in deciduous teeth with previous pulp treatment. In vitro study - Ariza Villanueva, Carola Maria (2021)
Objective: Compare the penetration of the conventional and modified Tri-antibiotic formula paste (3MIX-MP and 3MIX-P) in deciduous teeth in different with previous pulp treatment, in different periods of time. Methodology: 80 deciduous teeth that met the inclusion criteria were collected. Then conventional pulpectomy treatments were performed. The 3MIX-MP and 3MIX-P pastes were prepared. Once the paste was obtained, it was placed at the entrance of the root canals of the teeth and the final filling was made The times established to cut the teeth in each group were waited at 24, 48, 72 and 168 horas; the measurements were observed and carried out with the help of the stereoscopic microscope. Results: The 3MIX-MP paste penetrate to the level of the apical third of the obturated canal at 24, 48, 72 and 168 hours after treatment in the obturated canal and 3MIX-P paste manages to penetrate cervical third of the root canal at 24 hours after the treatment, but at 48, 72 and 168 hours it manages to penetrate up to the apical third. Conclusions: There is a difference in penetration 24 hours after the treatment in the obturated canal, the 3MIX-MP paste manages to penetrate to the apical third of the root canal, that is, it reaches the apical foramen and the 3MIX-P paste only penetrates up to the cervical third of the root canal. At 48, 72 and 168 hours both pastes (3MIX-MP, 3MIX-P) managed to penetrate up to the apical third.